Análisis comparativo de las campañas publicitarias del día de la madre 2023 realizadas por “RM” y “De Prati” - Solis Buenaire, Kimberly Galicia (2023)
Mother's Day campaigns tend to be popular for improving sales, therefore, this research presents a comparative analysis of the Mother's Day advertising campaigns of RM and De Prati, in order to provide beneficial information for both the brands themselves and for those who study the advertising campaigns. Answering what strategies and approaches they used in the campaigns. Starting from the objective of Determining the strategies used in RM and De Prati's Mother's Day advertising campaigns on their social networks in the year 2023. Exploring advertising themes, advertising campaign strategies and the most used channels, creative approaches, the position of the mother and woman in advertising and information about RM and De Prati. And making use of a qualitative, inductive and descriptive methodology highlighting the qualities of the campaigns and the elements that compose them through their characteristics and using documentary consultation techniques to establish a theoretical basis that allowed the correct handling of techniques and information and observation, with their respective observation sheets allowing to collect data from the publications of the Instagram page of RM and De Prati in the period from the beginning of May until Mother's Day. Resulting in digital strategies with social networks, making use of emotionality and influencers by both companies, but having a greater diversity of approaches by Rm, using emotionality, humor and storytelling, De Prati did not diversify as much, however, was the one who obtained more interaction in its account, leaving far behind the interaction in RM. Thus recommending greater attention to their networks and encourage audience participation in the comments, in addition to diversify in creative approaches.